Penyelesaian Tindak Pidana Ilegal Fishing: Asas Manfaat Diwilayah Hukum Pengadilan Perikanan Tanjungpinang - Efritadewi, Ayu; Syahputra, Irwandi; Novianti, Tri; Nuraiani, Lia; Widiyani, Heni (PROGRESIF: Jurnal Hukum, 2022)
The status of fish evidence resulting from the crime of illegal fishing in the last three years At the Tanjungpinang District Court, it was destroyed during the investigation stage. The purpose of this research is to find out the obstacles and legal settlement of fish resulting from the criminal act of Illegal Fishing in a review of the principle of benefit. The research method to be carried out is empirical juridical research. Juridical settlement of fish resulting from the criminal act of Illegal Fishing in the review of the principle of benefit at the Tanjungpinang Fisheries Court can actually be carried out through auctions and grants. Barriers to the use of fish resulting from the criminal act of Illegal Fishing at the Tanjungpinang Fisheries Court, namely the caught fish are mostly rotten before the legal case is completed or a court order is issued, The next problem is if the fish are auctioned, most of the fish are not sold, Another obstacle PSDKP Batam does not have a place frozen freezer storage for the fish. Another way to store the caught fish is to rent a place to the private sector, but the price associated with the rental will be of high value and will be detrimental to the State.